2004
DOI: 10.1080/01485010490484129
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OFTREMELLA AURANTIAON TESTOSTERONE AND CORTICOSTERONE PRODUCTIONS IN NORMAL AND DIABETIC RATS

Abstract: Tremella aurantia (TA) has been traditionally used as food and crude medicine in Chinese society. The polysaccharide isolated from the fruiting bodies of TA exhibits significant hypoglycemic activity in diabetic mouse models of insulin-dependent diabetes mellitus (IDDM) and non-insulindependent diabetes mellitus (NIDDM). Diabetes will cause sexual dysfunction in patients. In the present study, we examined if the treatment of TA on IDDM and NIDDM rats will restore steroidogenesis and then the reproductive funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…[121314151617] Polysaccharides of Tremella fuciformis have been reported to augment T-lymphocytes in the PBL proliferation and decrease the IL-2 activities in mouse splenocytes in vitro . [12] Jeong et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[121314151617] Polysaccharides of Tremella fuciformis have been reported to augment T-lymphocytes in the PBL proliferation and decrease the IL-2 activities in mouse splenocytes in vitro . [12] Jeong et al .…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that mushroom polysaccharides have various biological activities, such as antitumor,[12] antidiabetic,[13] anti-inflammatory,[14] immunomodulatory,[1516] and steroidogenic activities. [17] Tremella mesenterica (Heterobasidiomycetes), a yellow brain jelly mushroom, is a popular edible and medicinal mushroom in Asia. Its pharmacologically active polysaccharides make up 60-70% structural fruiting body polysaccharides and up to 20% of polysaccharides are glucuronoxylomannan (GX).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we demonstrated that oral administration of Tremella aurantia (TA) mycelium reduced plasma testosterone level in normal rats and the feeding of TA could not recover testosterone production in diabetic rats (Lo et al, 2004). Moreover, we have also illustrated that TM could suppress hCG-stimulated steroidogenesis in MA-10 cells with does-and time-dependent manners, and TM did not have any toxicity to the cells (Lo et al, 2005).…”
Section: Introductionmentioning
confidence: 90%